Pengaruh Penggunaan Celebrity Endorser Terhadap Implusive Buying Behavior Konsumen (Survey pada Scarlett Body Whitening di Kota Bandung, Indonesia) - Azzahra, Latifah; Nursholehah, Nabilah (Asosiasi Ahli Administrasi Indonesia, 2022)
Scarlett Body Whitening is a brand from Indonesia released by Felicya Angelista which is famous for its brightening product variants. One of the promotions carried out by Scarlett Body Whitening is using a celebrity endorser. Celebrity endorser is an advertisement with the support of a celebrity which is believed to make it easier for consumers to remember the product and can accelerate the emergence of brand awareness of the product so as to create high consumer buying interest in beauty products. Seeing the importance of promotion and increasing sales, this research is to find out